Is India's Right to Education Act a Rightful Share? Distributive Politics, Education and the Media. (October 2022) - Gilbertson, Amanda; Arnold, Ben
India's Right to Education Act contains a provision requiring private schools to educate underprivileged children without charging fees, hinting at a new politics of distribution akin to James Ferguson's notion of the 'rightful share'. Through analysis of coverage of this provision in English language newspapers, we argue that the role of the media in building legitimacy for a 'rightful share' is undermined: by critics' representations of a market-based distribution of education as more just; by supporters' use of traditional welfare language of compassion for the meritorious poor; and, by reports of implementation failures that undermine the value of social assistance. This points to the significance of universality, unconditionality and clear distributive logics to the concept of the 'rightful share'.